Analysis of distribution characteristics of COVID-19 in America based on space-time scan statistic - Zhao, Yuexu; Liu, Qiwei (Frontiers in Public Health, 2022)
Based on the epidemic data of Corona Virus Disease 2019 (COVID-19) in 50 states of the United States from December 2021 to January 2022, the spatial and temporal clustering characteristics of COVID-19 in the United States are explored and analyzed. Firstly, the retrospective spatio-temporal analysis is performed by using SaTScan 9.5, and seventeen incidence areas are obtained, and all of them have passed the significance test. Then, the reliability of the results is tested by the circular distribution method in the time latitude and the clustering method in the spatial latitude, further confirming that the retrospective spatio-temporal analysis accurately measures in time and reasonably divides regions according to the characteristics in space. The results of spatial-temporal cluster analysis show that the first-level clustering area of the epidemic has Connecticut, Rhode Island, New York, Massachusetts, New Hampshire and New Jersey from December 1st, 2021 to January 31st, 2022, with an average relative risk of 1.28. The second-level clustering area includes 18 states, with an average relative risk of 0.86. The relative risk can quantitatively reflect the risk degree of the epidemic area. According to the emergency situation, the resources are reasonably distributed and the corresponding measures are formulated. The results show that the incidence of COVID-19 in the United States has spatial aggregation. At present, the epidemic situation in the United States continues to expand. It is necessary to do a good job in epidemic prevention, reduce the infected population, and effectively control the epidemic.